Financial Hardship Associated With Cancer in the United States: Findings From a Population-Based Sample of Adult Cancer Survivors - Yabroff, K Robin; Dowling, Emily C; Guy, Jr, Gery P; Banegas, Matthew P; Davidoff, Amy; Han, Xuesong; Virgo, Katherine S; McNeel, Timothy S; Chawla, Neetu; Blanch-Hartigan, Danielle; Kent, Erin E; Li, Chunyu; et al. (Journal of clinical oncology, 2016)
To estimate the prevalence of financial hardship associated with cancer in the United States and identify characteristics of cancer survivors associated with financial hardship. We identified 1,202 adult cancer survivors diagnosed or treated at ≥ 18 years of age from the 2011 Medical Expenditure Panel Survey Experiences With Cancer questionnaire. Material financial hardship was measured by ever (1) borrowing money or going into debt, (2) filing for bankruptcy, (3) being unable to cover one's share of medical care costs, or (4) making other financial sacrifices because of cancer, its treatment, and lasting effects of treatment. Psychological financial hardship was measured as ever worrying about paying large medical bills. We examined factors associated with any material or psychological financial hardship using separate multivariable logistic regression models stratified by age group (18 to 64 and ≥ 65 years). Material financial hardship was more common in cancer survivors age 18 to 64 years than in those ≥ 65 years of age (28.4% v 13.8%; P < .001), as was psychological financial hardship (31.9% v 14.7%, P < .001). In adjusted analyses, cancer survivors age 18 to 64 years who were younger, female, nonwhite, and treated more recently and who had changed employment because of cancer were significantly more likely to report any material financial hardship. Cancer survivors who were uninsured, had lower family income, and were treated more recently were more likely to report psychological financial hardship. Among cancer survivors ≥ 65 years of age, those who were younger were more likely to report any financial hardship. Cancer survivors, especially the working-age population, commonly experience material and psychological financial hardship.